Efficacy of convalescent plasma for treatment of COVID-19 in Uganda - Kirenga, Bruce; Byakika-Kibwika, Pauline; Muttamba, Winters; Kayongo, Alex; Namakula, Olive Loryndah; Mugenyi, Levicatus; Kiwanuka, Noah; Lusiba, John; Atukunda, Angella; Mugume, Raymond; Ssali, Francis; Ddungu, Henry; et al. (BMJ Open Resp Res, 2021)
Convalescent plasma (CCP) has been studied as a potential therapy for COVID-19, but data on its efficacy in Africa are limited. Objective In this trial we set out to determine the efficacy of CCP for treatment of COVID-19 in Uganda. Measurements Patients with a positive SARS-CoV- 2 reverse transcriptase (RT)-PCR test irrespective of disease severity were hospitalized and randomized to receive either COVID-19 CCP plus standard of care (SOC) or SOC alone. The primary outcome was time to viral clearance, defined as having two consecutive RT-PCR- negative tests by day 28. Secondary outcomes included time to symptom resolution, clinical status on the modified WHO Ordinal Clinical Scale (≥1-point increase), progression to severe/ critical condition (defined as oxygen saturation <93% or needing oxygen), mortality and safety.
Keywords: Convalescent plasma; Treatment; COVID-19; Uganda